ChemInform Abstract: Palladium‐Catalyzed Intramolecular C—H Amidation: Synthesis and Biological Activities of Indolobenzazocin‐8‐ones. Issue 20 (25th April 2013) - Boonya‐udtayan, Sasiwadee; Eno, Meredith; Ruchirawat, Somsak; Mahidol, Chulabhorn; Thasana, Nopporn
Abstract The title compounds are evaluated for their cytotoxicity against four cancer cell lines.